Measuring Flourishing Among Internal Medicine and Psychiatry Residents - Kelly-Hedrick, Margot (J Grad Med Educ, 2020)
BACKGROUND: Many residents experience burnout, prompting national attention to well-being; however, well-being is not merely the absence of burnout. A recently developed measure of flourishing may provide insight on this important topic. OBJECTIVE: We investigated flourishing in a sample of medical residents. METHODS: Internal medicine residents and psychiatry residents at 2 residency programs responded to a cross-sectional online survey (December 2017–February 2018), which focused on the Flourish Index (FI) and Secure Flourish Index (SFI). Both measures generate scores ranging from a low of 0 to a high of 10. Participants were queried about quality of life, burnout, work-life balance, empathic concern, and sociodemographic characteristics. Simple and multiple linear regressions were performed to examine the relationship between FI/SFI and other variables. RESULTS: The response rate was 92% (92 of 101). Participants were found to have a mean FI score of 6.8 (SD = 1.6) and mean SFI score of 6.9 (SD = 1.6). Low quality of life, low work-life balance satisfaction, high emotional exhaustion, lower empathic concern, and having a pet were all significantly associated with lower FI scores (R(2) = 0.59; F[14, 69] = 7.10; P < .0001), indicating lesser flourishing, controlling for other variables. Similarly, low quality of life, high emotional exhaustion, lower empathic concern, and having a pet were all significantly associated with lower SFI scores (R(2) = 0.55; F[14, 69] = 6.06; P < .0001), controlling for other variables. CONCLUSIONS: In this sample, the flourishing indices were associated with well-being and burnout metrics.